2021
DOI: 10.1126/science.abg4493
|View full text |Cite
|
Sign up to set email alerts
|

The emerging plasticity of SARS-CoV-2

Abstract: The evolution of SARS-CoV-2 poses challenges for vaccines and immunotherapies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
156
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(166 citation statements)
references
References 13 publications
1
156
0
1
Order By: Relevance
“…Compared with wild-type viruses, the D614G mutation enhanced the ability of virus proliferation and transmission ( Daniloski et al, 2021 ). The N501Y strengthened the affinity with human ACE2 and the infectivity, while 501Y·V2 variant is more resistant to multiple monoclonal antibodies, convalescent plasma, and vaccinee sera partly due to the E484K substitution ( Cele et al, 2021 ; McCormick et al, 2021 ; Noh et al, 2021 ). Furthermore, Kemp et al found the virus population changed dynamically during convalescent plasma therapy, which was characterized by the emergence of a dominant virus carrying double mutates in the spike, including D796H in the S2 and ΔH69/ΔV70 in the N-terminal of the S1 ( Kemp et al, 2021 ).…”
Section: Molecular Evolution Of Sars-cov-2 In the Human Populationmentioning
confidence: 99%
“…Compared with wild-type viruses, the D614G mutation enhanced the ability of virus proliferation and transmission ( Daniloski et al, 2021 ). The N501Y strengthened the affinity with human ACE2 and the infectivity, while 501Y·V2 variant is more resistant to multiple monoclonal antibodies, convalescent plasma, and vaccinee sera partly due to the E484K substitution ( Cele et al, 2021 ; McCormick et al, 2021 ; Noh et al, 2021 ). Furthermore, Kemp et al found the virus population changed dynamically during convalescent plasma therapy, which was characterized by the emergence of a dominant virus carrying double mutates in the spike, including D796H in the S2 and ΔH69/ΔV70 in the N-terminal of the S1 ( Kemp et al, 2021 ).…”
Section: Molecular Evolution Of Sars-cov-2 In the Human Populationmentioning
confidence: 99%
“…While the SARS-CoV-2 Spike number is moderate compared to other enveloped viruses such as influenza, it is even lower for HIV-1 with 14 or fewer Env spikes incorporated into the viral membrane (Figure 1, Table 1) [95]. The high plasticity of HIV-1 and SARS-CoV-2, as characteristic for Retroviridae and Coronaviridae, and their potential to tolerate sequence and structural changes without critical loss of function has warranted their zoonotic transmission and ongoing evolutionary success [96,97].…”
Section: Viral Compositionmentioning
confidence: 99%
“…It implies that SARS-CoV-2 variants are converging based on common purifying selection processes. The associated appearance of mutations, e.g., in South African and Brazilian/Japanese variants at Spike positions 417, 484, and 501 indicate the importance of synergisms and compensatory mutations to fine-tune neutralization escape, infectivity, and replicative fitness [96,328]. Close monitoring of variants will remain crucial to identify emerging nAb escape variants and discern phylodynamic spread based on immune pressure from founder effects and sampling bias.…”
Section: Sars-cov-2 Mutates On a Low But Constant Level Yielding Mutant Variants Over Timementioning
confidence: 99%
“…Certainly, such an exercise could be repeated multiple times as new data become available from different locations around the World, but this is not the goal of our approach. Since the first revision of the manuscript in October 2020, the introduction of vaccines has contributed to bringing under control the trajectory of the Covid-19 virus 26,27,28,29 but the emergence of new variants and mutations 30,31,32 , most notably in India but also elsewhere, reminds us of possible challenges for vaccines and immunotherapies alike.…”
Section: Introductionmentioning
confidence: 99%